Social Engagement and Health: a Structural Equation Modelling Analysis of Downstream Links to Health Outcomes Among White-collar Professionals - (:unkn) unknown (My University, 2017)
ABSTRACT SOCIAL ENGAGEMENT AND HEALTH: A STRUCTURAL EQUATION MODELLING ANALYSIS OF DOWNSTREAM LINKS TO HEALTH OUTCOMES AMONG WHITE-COLLAR PROFESSIONALS by Ahmad Iqmer Nashriq bin Mohd Nazan The University of Wisconsin – Milwaukee, 2017 Under the Supervision of Associate Professor Amy E. Harley High level of social engagement has been associated with improved health outcomes. Its capacity to influence one’s health has led to the conception of Berkman’s social relationship model which hypothesizes that health is impacted by social relationship through a series of causal processes that begin at the macro-social level (upstream factors) to micro-psychobiological processes (downstream factors). Social engagement can be defined as the enactment of potential ties in real life activity but the mechanisms through which these ties impact health are scarcely investigated. Furthermore, existing evidences on these mechanisms or mediators are flawed and questionable. Studies have also shown that social engagement level among white-collar professionals are gradually fading given the damaging factors they experience at work. Nonetheless, social engagement has never been considered as a predictor of health status for these professionals despite its correlation with health. Using Berkman’s model as the guiding framework, the study sought to: a) investigate the relationship between social engagement and health among white-collar professionals, b) evaluate the influence of their job strain, working hours, age, race, education, and income on social engagement level, (c) assess the associations of social engagement with the model’s behavioral and psychological variables, and (d) determine which of these variables mediate the link between social engagement and health. The current study emphasized on white-collar professionals in Malaysia as the country’s diverse background provided unique opportunities for assessing social engagement from the perspective of different work and cultural ethics as well as religious beliefs following its multi-ethnic, multi-cultural, and multi-religious society. A two-phase recruitment approach was employed. First, participants were invited for a cognitive interview to pretest the instruments. Comments from n=9 participants were reviewed to revise the 14 instruments used in the survey. Second, recruitment for survey research was conducted through paper and web invitations yielding a final sample of n=200. Data were analyzed with Mplus using confirmatory factor analyses and structural equation modelling techniques. The study showed that social engagement correlated positively with health. It was also found that age and race predicted the social engagement level of the Malaysian professionals. Additionally, social engagement exhibited significant associations with some of the behavioral and psychological variables tested in the model which include diet, help seeking, self-efficacy, self-esteem, coping effectiveness, depression, and purpose in life. Of these, only depression was found to mediate the association between social engagement and health. The results provide empirical support for several key areas in the social engagement literature and could be used to inform future formative research of behavioral interventions.
Keywords: Health; Mediation Analysis; Social Engagement; Social Relationship; Structural Equation Modelling; White-collar Professionals